1998
DOI: 10.1097/00005392-199808000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Injection Therapy for Post-Prostatectomy Incontinence

Abstract: Transurethral collagen injection therapy is a reasonable treatment option for post-prostatectomy incontinence in select patients in whom more conservative therapy has failed. However, patients who have required a penile clamp, experienced continuous leakage or undergone transurethral incision of a bladder neck contracture are unlikely to respond well to this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 14 publications
3
37
0
3
Order By: Relevance
“…Although direct comparisons are lacking, historical data indicates that InVance supplants most of the techniques offered until now as alternatives to AUS. Bulking agents have been extensively used but 1-year success rates have generally been below 20% [9][10][11]. Proact TM balloons seem to provide a slightly better outcome but implantation is still associated with a high rate of balloon ruptures and consequent explantations [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although direct comparisons are lacking, historical data indicates that InVance supplants most of the techniques offered until now as alternatives to AUS. Bulking agents have been extensively used but 1-year success rates have generally been below 20% [9][10][11]. Proact TM balloons seem to provide a slightly better outcome but implantation is still associated with a high rate of balloon ruptures and consequent explantations [12].…”
Section: Discussionmentioning
confidence: 99%
“…These inconveniences may be exacerbated in elderly people. In a recent study, almost half of the sphincters implanted in patients in the seventh decade of life were removed, inactivated or revised [8] [9][10][11]. The bulking effect has also been achieved with plastic balloons placed near the bladder neck, but the continence rate is still low and the number of balloon ruptures is as high as 40% [12].…”
Section: Introductionmentioning
confidence: 99%
“…Collagen, silicon, teflon, carbon particles, autologous oil, durasphere, ethylene vinyl alcohol, polyetaphloretylene are used. Smith and et al (28) revealed that the 60-70% success with injection in short-term period and the success rate decreases during the long-term period. Furthermore, Cespedes et al (29) reported a 20% success rate for longterm period.…”
Section: Injectionmentioning
confidence: 99%
“…In one study, social continence (dry or one pad a day) was reported in more than 50% of patients at 3 months. 48 However, it is the duration of the continent interval that is the major issue. At a follow-up of 2 years, the continent rate has dropped to 30% and the new solid particles 49 have not significantly improved long-term results.…”
Section: Surgical Interventionsmentioning
confidence: 99%